Media pressure as a threat to the principle of criminal legality - López-González, Ronny (2023)
This article presents a general overview of the criminal legality concept explained in the First Article of the Criminal Code and the Criminal ProcedureCode of Costa Rica, as well as its practical application. In the same way, based on the theoretical postulates of the legal institute, we analize the excesses commited by the Costa Rican State against this principle due to the media’s pressure.